Spontaneous Pyogenic Choledochal Fistula - Pemmada, Vikas; Jain, Parvesh Kumar (Journal of Gastrointestinal Infections, 2024)
Spontaneous internal biliary fistulas (IBFs) are quite uncommon (<1%). These fistulas can develop between the gallbladder and bile duct with an internal organ, cavity, or a free surface. IBF is associated with chronic cholelithiasis in 90% of the cases. We report a rare case of choledochal fistula with an intra-abdominal abscess in a patient with chronic pancreatitis and diabetes mellitus, which were successfully managed with combined procedures of endoscopic retrograde cholangiopancreatography biliary stenting and ultrasound-guided drainage of the abscess.
Keywords: biliary fistula; abdominal abscess; chronic pancreatitis; ERCP; diabetes